BANKS OF THE CASPIAN REGION COUNTRIES IN THE BANKING SYSTEM OF RUSSIA: CURRENT TRENDS AND DEVELOPMENT PROBLEMS - Olga Viktorovna Bogacheva (Science and Innovation Center Publishing House, 2019)
The mutual penetration of capital from one country into another has become a characteristic feature of the world financial system. This is largely due to the current globalization processes in the global economy, the continuous development of banking technologies, the need to maintain foreign economic activity of business entities and the rationale for expanding the scales of business activity as a tool to increase operating efficiency.